Green suppler selection by an integrated method with stochastic acceptability analysis and MULTIMOORA - Mi, Xiaomei; Liao, Huchang; Liao, Yi; Lin, Qi; Lev, Benjamin; Al-Barakati, AbdullahI (Technological and Economic Development of Economy, 2020)
In the process of supplier selection for green supply chain management, uncertain information may appear in alternatives’ performances or experts’ preferences. The stochastic multicriteria acceptability analysis (SMAA) is a beneficial technique to tackling the uncertain information in such a problem and the MULTIMOORA is a robust technique to aggregate alternatives’ utilities. This study dedicates to proposing an SMAA-MULTIMOORA method by considering the advantages of both methods. The integrated method can accept uncertain information as inputs. The steps of the SMAA-MULTIMOORA are illustrated. A case study about the selection of green suppliers is given to show the validity and robustness of the SMAA-MULTIMOORA method.